PENGARUH INTERAKSI KOMITMEN ORGANISASI DAN PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN:STUDI PERILAKU MANAJER HOTEL DI MALANG RAYA - Kurniawan, Setia Budi (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
The relation betwen budgetary participation and budgetary slack has been examined in several accounting studies with conflicting result. Several researchers have found that budget slack occurs due to various individual behavioral factors in an organization. Participation in budgeting in organization is the part that can cause budget slack. One of the alternatives to reconcile these difference in finding is by using contingency approach, that is using motivational factors of organizational commitment as moderating variable. This research tries to conduct empirical tests for the effect of organizational commitment as moderating factor, the relation between participatory budgeting and budget slack. The result of the analysis shows that organizational commitment as moderating variable has direct influence on the relation between participatory budgeting with budget slack. The higher organizational commitment will decrease the budget slack for the individual who participates in the budgeting, while the lower organizational commitment will increase the the budget slack for the individual who participates in the budgeting.